Mathematics teachers’ knowledge-sharing on the Internet: pedagogical message in instruction materials - Liljekvist, Yvonne (NOMAD Nordic Studies in Mathematics Education, 2016)
This article reports on a study of teacher-shared documents containing mathematical tasks published on the Internet. The aim was to identify the goals, methods and pedagogical justifications presented in the documents and what was needed to solve the tasks. Content analysis was used to define their pedagogical message. The results show that the documents mainly involve content goals for younger pupils that are not consistent with the explicit descriptions. The conceptual goals are communicated to a great extent, but are not supported by task features. The reasons for why the tasks given are expected to lead to a certain goal are very often implicit, and, as a result, the content of the documents and the quality of the tasks are somewhat unclear to other teachers.